Penetrasi Papan Ketik Aksara Bali pada Pengguna Perangkat Mobile - Ida Bagus Ary Indra Iswara; Putu Praba Santika; I Nyoman Saputra Wahyu Wijaya (Badan Riset dan Inovasi Daerah Provinsi Bali, 2019)
The Balinese language which is used in daily life on the island of Bali has experienced a shift in usage so it needs to be preserved. In an effort to preserve the Balinese language and script, the Provincial Government issued Bali Governor Regulation Number 20 of 2013 and Regulation number 1 of 2018. I Made Suatjana submitted a proposal that the Balinese script be included in Unicode to make it easier to display Balinese script on digital media. Cokorda Rai Adi Pramartha developed keyboards or keyboards and an application called T@miang to facilitate typing Balinese characters on computer devices. Computer equipment is slowly becoming obsolete, replaced by mobile devices used by 53.03% of users in Indonesia, so it is necessary to build a Balinese script keyboard that can be used on mobile devices. PaTik Bali is built for mobile devices with Android operating system. PaTik Bali layout is adapted to T@miang keyboard layout. PaTik Bali version 1.0 only uses the Balinese script on each keyboard key. In version 2.0 each button on PaTik Bali has been added Latin letters because of the large number of entries on the Google Play page. Based on data recorded on the Google Play Console, there are 41,820 devices that have installed the Balinese Keyboard (PaTik Bali) application, 99.19% are from Indonesia. In general, the PaTik Bali application can be accepted in the community, this can be seen from the average rating given by users on Google Play which is 4.27 on a scale of 5. However, some users complain about the incorrect form of letters. The PaTik Bali application uses fonts that have been embedded in the Android operating system so that it can be used as a keyboard in other applications. This font still has enough problems. To fix this problem, it is necessary to develop the Balinese font then ask Google as an Android developer to enter the new font into the Android operating system.